Poder e sexualidade: a mulher bruxa na narrativa de Anne Rice - Ayda Elizabeth Blanco Estupiñán (2020)
This PhD dissertation constitutes a feminist reading of the novels The witching hour (1990) and Lasher (1993), from the trilogy “The lives of the Mayfair witches” by the Ameri-can writer Anne O’Brien Rice. The analysis presented is based on the feminist theory about power and sexuality and the view of the witch as protagonist. The most representative his-torical elements about women are presented as a part of the research methodology, since they validated the witchery definition as a crime almost exclusively of women, and por-trayed the witch as a feminist character. Furthermore, the witch is related to the appropria-tion and interpretation of herself in feminism, and to the studies about the witch hunt, based on gender category. The analysis developed here shows the relevance of the witch as an archetypical figure that is linked to transgression. It also depicts social relationships be-tween men and women based on predominant patriarchal logic, and on negative and lessen-ing ideas about the woman. This investigation focuses on how Rice discusses, through the witch character, topics common to the interpretation of the character and the theory about power and sexuality, generated in the second feminist wave.